The Effect of Explant Types and Kinetin Concentration on In Vitro Callus Induction in Vetiveria zizanioides (L.) Nash - Arbaul Fauziah; Wahyu Widoretno (Journal of Experimental Life Science)
The aims of this research were to evaluate the effect of explant types and several kinetin concentrations on in vitro induction and growth of callus vetiver (Vetiveria zizanioides (L.) Nash). Crown and tiller of vetiver were cultured on Murashige and Skoog’s (MS) media supplemented with combination of 2,4-D 0.75 ppm and several kinetin concentrations (0, 0.3, 0.5, 0.75, and 1) ppm. The induction and growth of callus were influenced by type of explant and concentration of kinetin. Formation and growth of callus on tiller explant were faster than crown explant. Callus on tiller explant were formed one week after culture, while callus from crown explant were formed at four weeks after culture. Callus growth on tiller explant also was better than crown explant. Eight weeks after culture, callus fresh weight from tiller explant was 0.35 ± 0.09 g, while callus fresh weight from crown explant was only 0.16 ± 0.08 g. The addition of kinetin in the medium combined with 2,4-D was able to increase callus growth and the optimum concentration of kinetin used was 0.5 ppm. The addition of kinetin more than 0.5 ppm in the medium decreased the callus fresh weight.